1994
DOI: 10.1111/j.2517-6161.1994.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Index of Fit Based on Mixture Methods for the Analysis of Contingency Tables

Abstract: A framework based on mixture methods is proposed for evaluating goodness of fit in the analysis of contingency tables. For a given model H applied to a contingency table P, we consider the two-point mixture P = (I -1I")H t + 1I"H 2 , with 11" the mixing proportion (0~11"~1) and HI and H 2 the tables of probabilities for each latent class or component. In the unstructured approach recommended here, the mixture model applies H to HI but does not impose any restrictions on H 2 • A contingency table P can generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(125 citation statements)
references
References 28 publications
(40 reference statements)
1
122
0
2
Order By: Relevance
“…This is the idea underlying the mixture index of fit proposed by Rudas et al, (1994). Let (1 ) p) denote the relative size of the fraction where the model fits and p that of the fraction where the model does not fit.…”
Section: The Mixture Approach To Handling Missing Datamentioning
confidence: 99%
“…This is the idea underlying the mixture index of fit proposed by Rudas et al, (1994). Let (1 ) p) denote the relative size of the fraction where the model fits and p that of the fraction where the model does not fit.…”
Section: The Mixture Approach To Handling Missing Datamentioning
confidence: 99%
“…Following Rudas et al [1], for a given model H applied to a contingency table P the twocomponent mixture…”
Section: The Rcl Index Of Fit and Rater Agreementmentioning
confidence: 99%
“…Whereas in the case of very large sample sizes, as argued in Rudas et al (Reference [1], p. 623), the concept of statistical signi"cance may become meaningless or even misleading, in the case of (very) small sample sizes, the sparseness of the data may raise doubts that the asymptotic properties of the conventional chi-squared goodness-of-"t statistics hold. Rudas et al [1] demonstrated the usefulness of their "t index for large samples; that the RCL mixture approach remains applicable to small samples resulting in empty cells will be shown here. As a consequence, the RCL index of "t may be recommended as a supplement to conventional goodness-of-"t tests in the presence of moderate sample sizes, and as their alternative in extreme situations of sample sizes.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations